2001
DOI: 10.1128/jvi.75.16.7683-7691.2001
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Intranuclear Distribution of Unintegrated Human Immunodeficiency Virus Type 1 DNA

Abstract: The RNA genome of human immunodeficiency virus type 1 (HIV-1) is converted into DNA after infection in order to integrate into the host cell DNA. However, a large number of these reverse-transcribed genomes remain unintegrated in the nucleus of infected cells. Currently, there are no data available about the intranuclear distribution pattern of unintegrated HIV-1 DNA in relation to nuclear structures as observed on the single-cell level. In the present study, we investigated the intranuclear fate of unintegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 62 publications
7
47
0
Order By: Relevance
“…However, while attachment to the primary target (i.e., carrier) cell is not pseudotype restricted, the susceptibility of secondary tissue targets remains subject to the specific interaction of vector envelope protein with its cognate cell surface receptor. Thus, for in vivo applications of vectorexposed cells, the combination of extended VSV-G tissue tropism and the ability of lentivirus vectors to transduce nondividing cells may lead to off-target transduction (3,22,37). Recent promising Env-based targeting approaches conferring tissue-restricted entry may be suitable in reducing off-target transduction in secondary tissues (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, while attachment to the primary target (i.e., carrier) cell is not pseudotype restricted, the susceptibility of secondary tissue targets remains subject to the specific interaction of vector envelope protein with its cognate cell surface receptor. Thus, for in vivo applications of vectorexposed cells, the combination of extended VSV-G tissue tropism and the ability of lentivirus vectors to transduce nondividing cells may lead to off-target transduction (3,22,37). Recent promising Env-based targeting approaches conferring tissue-restricted entry may be suitable in reducing off-target transduction in secondary tissues (41).…”
Section: Discussionmentioning
confidence: 99%
“…Bell et al [125] reported that no significant relationship was observed between ND10 or any of the following: HIV-1 DNA, transcription foci, and integrated DNA. Their results showed that HIV-1 did not modify ND10 at early or late times of infection [125] .…”
Section: Rna Virusesmentioning
confidence: 99%
“…Bell et al [125] reported that no significant relationship was observed between ND10 or any of the following: HIV-1 DNA, transcription foci, and integrated DNA. Their results showed that HIV-1 did not modify ND10 at early or late times of infection [125] . However, Turelli et al [126] reported that incoming retroviral preintegration complexes trigger the exportingmediated cytoplasmic export of PML.…”
Section: Rna Virusesmentioning
confidence: 99%
“…Even though FISH is a powerful technique, it is not very sensitive for HIV-1 detection and moreover disrupts the native architecture of the nuclear compartment as it requires harsh denaturation conditions. In addition, this technique does not allow the discrimination between integrated and nonintegrated viral DNA (16,17). Here we describe a fluorescent approach to visualize HIV-1 DNA in the nuclear compartment of infected cells.…”
mentioning
confidence: 99%